IDENTIFICATION OF DUMBEG IN ETHNOSCIENCE STUDIES AS A SOURCE OF SCIENCE LEARNING IN REMBANG SOCIETY - Wahyuni, Sri; Fawaida, Ulya (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
Culture has a positive impact when studied more deeply. Culture is one of the characteristics of a region. Dumbeg is one of the typical foods that has ethnoscience studies in it. Contextual-based learning by utilizing phenomena that exist in nature such as local culture is very important so that students can preserve the existing local culture. The purpose of this study is to study ethnoscience in the manufacture of dumbeg in Rembang district as a source of science learning. The method in this study uses observation and interviews with informants. The results of this study are 1) Culture and science have a strong relationship so that ethnoscience can be used as a source of learning in the world of education. 2) The process of making dumbeg is one example of the correlation between science and culture. 3) Local dumbeg culture can be used as a source of science learning, both physics and biology.